Pembinaan Kegiatan Olahraga Gerakan Masyarakat Sehat di Desa Karanghaur - Kisanda Midisen; Sakum; Sarwo Edy; Rini Setyowati; Siti Juariah (DPPM Universitas Pelita Bangsa, 2021)
Physical activity has become a common practice among modern people. For young adults, physical activity provides various benefits including improved motor function and cardiopulmonary function. As the new generation of the nation, youth plays an important role in the growth and development of Indonesia. Thus, higher education plays an important role in the development of sports personnel, both in terms of hard skills and soft skills. Based on the observed problems, the proposed solution in the Kelurahan is to hold counselling on the health benefits of exercise, conduct aerobic exercises, hold sports discussions directly and WhatsApp, and conduct regular joint sports activities. After promoting the health benefits of physical activity, various sports organisations and groups sprung up into a community, including football, volleyball, sports, and badminton groups. During the transaction, people were very happy and took the action seriously to show the importance of exercise for health. The nationwide enthusiasm for this social initiative saw participants from various fields and raised many questions about the benefits of exercise. The formation of various communities and sports groups signalled the public's awareness of the importance of physical activity in improving health and quality of life. The socialisation was successful in increasing people's knowledge about health sports and its positive impact on physical, mental and social aspects. The suggestion is for continuous promotion and counselling activities on the benefits of exercise so that public awareness continues to increase.